2022
DOI: 10.1177/13678779221091293
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctions of resilience and the Covid-19 crisis of the creative cultural industries

Abstract: This article compares the conjunctions of emergency resilience and ecological resilience that underpin the creative cultural industry (CCI) crisis. It first introduces three characteristics that socially construct the CCI crisis and its hegemonic practice of emergency resilience (time, disaster discourse, and the adaptation of aesthetic digitalization) and exposes multiple discourses – from the technologies of cultural statistics to corporate financial modelling – that construct an ideology of ‘resilience-as-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The cultural and creative industries have been an important site for resilience scholarship (Comunian and England, 2020; Frauts, 2019; Jennings et al, 2016; Khlystova et al, 2022; Newsinger and Serafini, 2021; Pasquinelli and Sjöholm, 2015, Yue, 2022). Pratt (2017: 136) argues that ‘the cultural field is “born resilient’” because ‘radical market uncertainty and risk … characterizes the cultural field’.…”
Section: The Concept Of Resiliencementioning
confidence: 99%
See 2 more Smart Citations
“…The cultural and creative industries have been an important site for resilience scholarship (Comunian and England, 2020; Frauts, 2019; Jennings et al, 2016; Khlystova et al, 2022; Newsinger and Serafini, 2021; Pasquinelli and Sjöholm, 2015, Yue, 2022). Pratt (2017: 136) argues that ‘the cultural field is “born resilient’” because ‘radical market uncertainty and risk … characterizes the cultural field’.…”
Section: The Concept Of Resiliencementioning
confidence: 99%
“…Scholars have recently began to turn from the ‘emergency resilience’ framing that has dominated the creative industries and instead focus on other facets of resilience (Yue, 2022). Yue (2022: 2) offers a conceptualization of ‘ecological resilience’ in the creative industries, for example ‘long-term adaptability through creative iteration and transformation’. Here the focus is on what makes resilience sustainable, durable, and continuous.…”
Section: The Concept Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…The outbreak of the COVID‐19 pandemic tested the resilience of state institutions (Colfer, 2020) and made the scientific community gradually shift toward approaches of “ecological resilience” (Arts Council England, 2018; Frigotto et al, 2022). As a property of an entire system, rather than a quick mitigation of emergencies, resilience becomes related to a longer term, transformative process in which capabilities such as a willingness to learn, perseverance, the ability to innovate, and flexibility at the system's level come into play (Yue, 2022).…”
Section: Resilience Defined and State Of Researchmentioning
confidence: 99%
“…For example, Pratt (2017) showed that the arts and cultural sectors were among the few sectors that were able to overcome the financial crisis of 2008/2009 in the United Kingdom, because of its multifaceted, complex forms of organization and finance (“nonnormative organizational structure”; Pratt, 2017, p. 136), but it “has been achieved by the socialisation of risk through temporary and unpaid labour, and through outsourcing innovation and training” (Pratt, 2017, p. 137). Further, resilience has been considered to be emergent (not emergency), iterative (not rebound), and transformative (not back to normal), entailing a promise to build “a wholistic cultural ecology that can nurture fair work, artistic innovation, economic growth and cultural vitality” (Yue, 2022, p. 362). The reawakened importance of resilience in the cultural domain during the pandemic conveys an image of resilience as “emergency preparedness” (Yue, 2022, p. 352).…”
Section: Resilience Defined and State Of Researchmentioning
confidence: 99%